2021
DOI: 10.1155/2021/9986550
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mycoplasmas and Cancer: Is It Fact or Fiction ? Narrative Review and Update on the Situation

Abstract: More than one million new cancer cases occur worldwide every year. Although many clinical trials are applied and recent diagnostic tools are employed, curing cancer disease is still a great challenge for mankind. Heredity and epigenetics are the main risk factors often related to cancer. Although, the infectious etiological role in carcinogenesis was also theorized. By establishing chronic infection and inflammation in their hosts, several microorganisms were suggested to cause cell transformation. Of these su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…These studies concluded that mycoplasmas infection stimulates tumorigenesis by inducing cellular transformation. Yacoub et al (2021) have demonstrated the possible relationship between mycoplasmas infection and the development of cancers. In parallel, they reported the induction of malignant transformation by mycoplasmas infection in PMNCs (Zhang et al, 2004) and in many other human cell lines such as the uterus SK-UT-1B cells (Polianskaia et al, 1998), A549 lung cells and bone tissues (Jiang et al, 2008), prostate BPH-1 cells (Namiki et al, 2009), and neuronal cell lines (Ji et al, 2019).…”
Section: Mycoplasma Infection and Cancersmentioning
confidence: 99%
“…These studies concluded that mycoplasmas infection stimulates tumorigenesis by inducing cellular transformation. Yacoub et al (2021) have demonstrated the possible relationship between mycoplasmas infection and the development of cancers. In parallel, they reported the induction of malignant transformation by mycoplasmas infection in PMNCs (Zhang et al, 2004) and in many other human cell lines such as the uterus SK-UT-1B cells (Polianskaia et al, 1998), A549 lung cells and bone tissues (Jiang et al, 2008), prostate BPH-1 cells (Namiki et al, 2009), and neuronal cell lines (Ji et al, 2019).…”
Section: Mycoplasma Infection and Cancersmentioning
confidence: 99%
“…Mycoplasmas can promote low-grade chronic inflammatory conditions without killing the cells. Thus, they were thought to be ideal for promoting carcinogenesis ( Yacoub et al, 2021 ). Xiaolei et al found that the prevalence and the pathogenic load of U. urealyticum were significantly higher in the cervical cancer group compared to the control group ( Xiaolei et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of mycoplasma infection and the consequent chronic inflammation leads to a progressive malignant transformation, increasing the in vitro invasiveness and in vivo metastasis of different human tumor cells [ 162 ]. Epidemiologic studies demonstrated the association of several mycoplasma species with different kinds of tumors [ 163 ]. M. hominis , Ureaplasma parvum , and Ureaplasma urealyticum are tightly associated with prostate cancer [ 136 , 162 , 164 , 165 ].…”
Section: Relevance Of Nets To Immunity and Mycoplasma Acute And Chron...mentioning
confidence: 99%